Magnetic transition metal-based composite material and preparation method and application thereof
Patent Information
- Application Number
- CN202510423040.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明的主要目的在于提供一种磁性过渡金属基复合材料及其制备方法与应用,以克服现有技术中吸附剂制备工艺复杂、吸附速率慢、吸附容量低、难以分离等不足
[0017] (1) The magnetic transition metal matrix composite material provided by the present invention has good adsorption performance for methylene blue dye. Under the conditions of complete light protection and room temperature, the adsorption capacity is large and the removal efficiency is high, which is at a relatively excellent level among similar adsorption materials. Moreover, the prepared magnetic transition metal matrix composite material has good magnetism and is easy to separate and recover from the solution.
Smart Images

Figure CN122912796A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adsorption materials technology, specifically relating to a magnetic transition metal matrix composite material, its preparation method, and its application. Background Technology
[0002] Due to technical challenges in the dyeing and printing industry, a large amount of dye wastewater is inevitably generated during production. The discharge of this wastewater not only affects water quality safety but also endangers human health. Therefore, efficient purification before discharge is crucial. Methylene blue is one of the most common dyes, widely used in the textile industry. Studies have shown that prolonged exposure to methylene blue can cause skin damage, while direct ingestion can lead to increased heart rate, digestive system diseases, and methemoglobinemia. Therefore, there is an urgent need for efficient removal of methylene blue from wastewater to reduce threats to humans and ecosystems. Currently, various methods exist for removing methylene blue dye from water, including photocatalysis, adsorption, Fenton oxidation, and membrane filtration. Among these methods, adsorption is the most widely used due to its advantages of simplicity, low cost, and wide applicability. However, the slow adsorption rate, low adsorption capacity, and difficulty in separation of traditional adsorbents limit their application. Therefore, developing a novel adsorbent material capable of efficiently removing dyes from water is particularly necessary.
[0003] Patent CN1 16651386A uses layered molybdenum boride as a growth template to obtain NiCo LDH / MoB material by solvent loading of nickel-cobalt layered double hydroxides. This material is then modified with salts and acidic substances to obtain a composite material. This material exhibits adsorption capacities of 307.5 mg / g for methyl orange and 83.2 mg / g for methylene blue, with removal rates reaching 97.3% and 91.7%, respectively. However, the preparation process of this patent is relatively complex and involves numerous steps.
[0004] Patent CN111957298A prepared K3PMo using phosphomolybdic acid, potassium chloride, and nickel dimethylglyoxime as raw materials via solution reaction. 12 O 40 The [Ni(DMG)2] composite material is used to adsorb organic dyes. However, the preparation process of this patent is complex and the maximum adsorption capacity for methylene blue is only 10 mg / g.
[0005] Patent CN1 16870879A synthesizes an adsorbent capable of rapidly adsorbing methylene blue dye from water by combining polyoxometalates with metal salts and organic ligands via a hydrothermal reaction. This allows the polyoxometalates to participate in the construction of the metal salt and organic ligand framework (forming MOFs). The removal rate of methylene blue can reach 99.69% within 2 minutes. However, the preparation process of this patent is complex and cumbersome, and the maximum adsorption capacity for methylene blue is relatively low.
[0006] In summary, existing technologies suffer from drawbacks such as complex adsorbent preparation processes, slow adsorption rates, low adsorption capacity, and difficulty in separation. Summary of the Invention
[0007] The main objective of this invention is to provide a magnetic transition metal matrix composite material, its preparation method, and its application, so as to overcome the shortcomings of existing technologies such as complex adsorbent preparation processes, slow adsorption rates, low adsorption capacity, and difficulty in separation.
[0008] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:
[0009] One aspect of the present invention provides a method for preparing a magnetic transition metal matrix composite material, comprising:
[0010] A metal chelate is obtained by mixing and drying a metal salt solution with a ligand; the metal chelate is then calcined in a protective atmosphere to obtain a magnetic transition metal matrix composite material; wherein the metal salt in the metal salt solution includes at least one of nickel salt and iron salt.
[0011] Another aspect of the present invention provides a magnetic transition metal matrix composite material prepared by the said preparation method.
[0012] Another aspect of the present invention provides the application of the magnetic transition metal matrix composite material in the field of dye wastewater treatment.
[0013] Another aspect of the present invention provides a method for treating dye wastewater, comprising:
[0014] Provide the magnetic transition metal matrix composite material;
[0015] The magnetic transition metal matrix composite material is mixed with dye wastewater to carry out an adsorption reaction to adsorb the dye.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects:
[0017] (1) The magnetic transition metal matrix composite material provided by the present invention has good adsorption performance for methylene blue dye. Under the conditions of complete light protection and room temperature, the adsorption capacity is large and the removal efficiency is high, which is at a relatively excellent level among similar adsorption materials. Moreover, the prepared magnetic transition metal matrix composite material has good magnetism and is easy to separate and recover from the solution.
[0018] (2) The magnetic transition metal matrix composite material provided by the present invention has a simple preparation process, a wide range of raw material sources, and low cost, and has great practical value and application prospects in the field of dye wastewater treatment. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 These are the X-ray diffraction patterns of the magnetic transition metal matrix composites prepared in Examples 1, 2 and Comparative Example 6 of this invention;
[0021] Figure 2 These are the X-ray diffraction patterns of the magnetic transition metal matrix composites prepared in Examples 1, 1, and 2 of this invention.
[0022] Figure 3 This is an adsorption curve of the magnetic transition metal matrix composite material prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention.
[0023] Figure 4 This is an adsorption curve of the magnetic transition metal matrix composite material prepared in Example 2, Comparative Example 4 and Comparative Example 5 of the present invention.
[0024] Figure 5 This is a graph showing the change in the removal rate of dyes of different concentrations by the magnetic transition metal matrix composite material prepared in Example 1 of the present invention over time. Detailed Implementation
[0025] In view of the problems existing in the prior art, the inventors of this invention have conducted extensive and in-depth research and have provided a magnetic transition metal matrix composite material, its preparation method and application.
[0026] The following will provide a further explanation of the technical solution, its implementation process, and its principles.
[0027] As one aspect of the technical solution of this invention, a method for preparing a magnetic transition metal matrix composite material includes:
[0028] A metal chelate is obtained by mixing and drying a metal salt solution with a ligand; the metal chelate is then calcined in a protective atmosphere to obtain a magnetic transition metal matrix composite material; wherein the metal salt in the metal salt solution includes at least one of nickel salt and iron salt.
[0029] In some embodiments, the preparation method of the magnetic transition metal matrix composite material specifically includes: mixing a metal salt with water to form a metal salt solution.
[0030] In some preferred embodiments, the concentration of the metal salt solution is 0.1–3 mol / L.
[0031] In some embodiments, the nickel salt includes at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel acetate, etc., but is not limited to this.
[0032] In some embodiments, the iron salt includes at least one of ferric chloride, ferric sulfate, ferric nitrate, etc., but is not limited thereto.
[0033] In some embodiments, the ligand in the ligand solution includes at least one of sodium citrate, sodium diethylenetriaminepentaacetate, disodium ethylenediaminetetraacetate, sodium sulfosalicylate, etc., but is not limited thereto.
[0034] In some embodiments, the preparation method of the magnetic transition metal matrix composite material specifically includes: mixing a ligand with water to obtain a ligand solution.
[0035] In some preferred embodiments, the concentration of the ligand solution is 0.1–3 mol / L.
[0036] In some preferred embodiments, the stirring is carried out at 50–100°C for 1–10 minutes.
[0037] In some embodiments, the preparation method of the magnetic transition metal matrix composite material specifically includes: mixing the metal salt solution with a ligand solution to carry out a coordination reaction, and drying to obtain the metal chelate. The metal chelate is in powder form.
[0038] In some preferred embodiments, the molar ratio of the metal salt to the ligand is 1:1 to 1:5.
[0039] In some preferred embodiments, the coordination reaction is carried out at a temperature of 50–100°C for a time of 2–6 hours.
[0040] In some preferred embodiments, the drying temperature is 50–100°C and the time is 8–24 hours.
[0041] In some embodiments, the preparation method of the magnetic transition metal matrix composite material specifically includes: calcining the metal chelate in a protective atmosphere, cooling and grinding it to obtain the magnetic transition metal matrix composite material.
[0042] In some preferred embodiments, the metal chelate is heated in a protective atmosphere at a rate of 2 to 10 °C / min.
[0043] In some preferred embodiments, the protective atmosphere comprises nitrogen.
[0044] In some preferred embodiments, the calcination temperature is 700–850°C and the time is 60–180 min.
[0045] In some more specific embodiments, the preparation method of the magnetic transition metal matrix composite material may include the following steps:
[0046] (1) Dissolve the metal salt completely in water to obtain a metal salt solution with a concentration of 0.1 to 3 mol / L;
[0047] (2) Add the complexing agent to water and stir at 50-100℃ for 1-10 min to obtain a complexing agent solution of 0.1-3 mol / L;
[0048] (3) The ligand solution and the metal salt solution are mixed in a molar ratio of 1:1 to 1:5, and the mixed solution is subjected to a coordination reaction at 50 to 100°C for 2 to 6 hours. Then the mixture is dried at 50 to 100°C for 8 to 24 hours to obtain the metal chelate.
[0049] (4) The metal chelate is heated to 700-850°C in a protective atmosphere at a heating rate of 2-10°C / min and held for 60-180 min. After cooling to room temperature, it is ground to obtain the magnetic transition metal matrix composite material.
[0050] In the preparation method of the present invention, the role of the metal salt is to provide the central ion and the source of magnetism; the role of the ligand is to provide the complex ion; the reaction mechanism is that the metal salt ion and the ligand undergo a coordination reaction to generate a metal chelate, and different magnetic transition metal matrix composite materials are obtained by calcination at different temperatures.
[0051] As another aspect of the technical solution of the present invention, a magnetic transition metal matrix composite material prepared by the aforementioned preparation method is provided. The magnetic transition metal matrix composite material is a black powder.
[0052] As another aspect of the technical solution of the present invention, it provides the application of the magnetic transition metal matrix composite material in the field of dye wastewater treatment.
[0053] As another aspect of the technical solution of the present invention, it also provides a method for treating dye wastewater, comprising:
[0054] Provide the magnetic transition metal matrix composite material;
[0055] The magnetic transition metal matrix composite material is mixed with dye wastewater to carry out an adsorption reaction to adsorb the dye.
[0056] In this invention, the magnetic transition metal matrix composite material adsorbs dyes through ultra-fast degradation primarily driven by electron interactions, which differs from traditional adsorption.
[0057] In some embodiments, the dye includes methylene blue.
[0058] In some implementation schemes, the concentration of dye in the dye wastewater is 10–600 mg / L.
[0059] In some embodiments, the mass ratio of the magnetic transition metal matrix composite to the dye is 1:1 to 1:3.
[0060] In some embodiments, the adsorption reaction is carried out at a temperature of 20–30°C for a time of 1–360 min.
[0061] In some embodiments, the method for treating dye wastewater achieves a dye removal rate of over 99%.
[0062] The magnetic transition metal matrix composite material provided by this invention has excellent adsorption performance for methylene blue dye. Under completely dark conditions and room temperature conditions, it has a large adsorption capacity and high removal efficiency, which is at a relatively excellent level among similar adsorption materials. It has great practical value and application prospects in the field of dye wastewater treatment.
[0063] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Modifications or equivalent substitutions made by those skilled in the art based on their understanding of the technical solutions of this invention, without departing from the spirit and scope of the invention, should all be covered within the protection scope of this invention.
[0064] For experiments not specifically described in the examples, the procedures or conditions can be performed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available. Other unmentioned raw materials and instruments are all conventionally chosen and do not involve the core technical means of this invention.
[0065] Example 1
[0066] Step (1): Mix 0.185 mol / L disodium ethylenediaminetetraacetate (EDTA-2Na) solution and 0.37 mol / L nickel nitrate (Ni(NO3)2) solution (where EDTA-2Na and Ni... 2+ The molar ratio of the two solutions was 1:1, and the mixture was stirred continuously at 80°C for 3 hours.
[0067] Step (2): Dry the solution obtained in step (1) at 80°C for 12 hours to obtain a metal chelate.
[0068] Step (3): The metal chelate obtained in step (2) is calcined at 800°C for 120 min under nitrogen protection at a heating rate of 5°C / min. After cooling to room temperature, it is ground to obtain a magnetic transition metal matrix composite material.
[0069] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution can reach more than 1000 mg / g within 1 min, and the removal rate can reach 99%.
[0070] Example 2
[0071] Step (1): Mix 0.185 mol / L disodium ethylenediaminetetraacetate (EDTA-2Na) solution and 0.37 mol / L ferric nitrate (Fe(NO3)3) solution (where EDTA-2Na and Fe... 3+ The molar ratio of the two solutions was 1:1, and the mixture was stirred continuously at 80°C for 3 hours.
[0072] Step (2): Dry the solution obtained in step (1) at 80°C for 12 hours to obtain a metal chelate.
[0073] Step (3): The metal chelate obtained in step (2) was calcined at 800°C for 120 min under nitrogen protection at a heating rate of 5°C / min. After cooling to room temperature, it was ground to obtain a magnetic transition metal matrix composite material.
[0074] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution can reach more than 1000 mg / g within 360 min, and the removal rate can reach more than 99%.
[0075] Example 3
[0076] The experimental procedure is the same as in Example 1, except that the calcination temperature is 700℃.
[0077] Example 4
[0078] The experimental procedure is the same as in Example 1, except that the calcination temperature is 850℃.
[0079] Example 5
[0080] The experimental procedure is the same as in Example 1, except that the molar ratio of nickel nitrate to disodium ethylenediaminetetraacetate is 1:3.
[0081] Example 6
[0082] The experimental procedure is the same as in Example 1, except that the molar ratio of nickel nitrate to disodium ethylenediaminetetraacetate is 1:5.
[0083] Example 7
[0084] The experimental steps are the same as in Example 2, except that the metal salt is ferric nitrate and the ligand is sodium diethylenetriaminepentaacetate.
[0085] Comparative Example 1
[0086] The experimental procedure is the same as in Example 1, except that the calcination temperature is 600℃.
[0087] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution within 1 min is only 209 mg / g, and the removal rate is only 20%.
[0088] Comparative Example 2
[0089] The experimental procedure is the same as in Example 1, except that the calcination temperature is 450℃.
[0090] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution within 1 min is only 79 mg / g, and the removal rate is only 7.6%.
[0091] Comparative Example 3
[0092] The experimental procedure is the same as in Example 1, except that the calcination temperature is 900℃.
[0093] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution within 1 min is only 13 mg / g, and the removal rate is only 1.2%.
[0094] Comparative Example 4
[0095] The experimental procedure is the same as in Example 2, except that the calcination temperature is 600℃.
[0096] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution is 930 mg / g within 1 min, and the removal rate is 89%.
[0097] Comparative Example 5
[0098] The experimental procedure is the same as in Example 2, except that the calcination temperature is 450℃.
[0099] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution within 1 min is 710 mg / g, and the removal rate is 68%.
[0100] Comparative Example 6
[0101] The experimental procedure is the same as in Example 1, except that the metal salt solution is a cobalt nitrate solution.
[0102] When the amount of magnetic transition metal matrix composite material is 0.5 g / L, the adsorption capacity of 520 mg / L methylene blue solution within 1 min is 275 mg / g, and the removal rate is 26%.
[0103] Figure 1 The X-ray diffraction patterns of the magnetic transition metal matrix composites prepared in Examples 1, 2, and Comparative Example 6 of this invention are shown. Figure 1 It can be seen that the surfaces of the magnetic transition metal matrix composites prepared in Examples 1, 2 and 6 are mainly the corresponding zero-valent metals.
[0104] Figure 2 The X-ray diffraction patterns of the magnetic transition metal matrix composites prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention are shown. Figure 2 It can be seen that the magnetic transition metal matrix composite material prepared in Comparative Example 2 exhibits characteristic peaks indicating the coexistence of Ni3C and zero-valent Ni, while the magnetic transition metal matrix composite material prepared in Example 1 mainly shows zero-valent Ni. This suggests that as the calcination temperature increases, nickel-containing species are gradually reduced to zero-valent Ni.
[0105] Figure 3 The adsorption capacity curves of the magnetic transition metal matrix composites prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are shown. Figure 3 As can be seen, the magnetic transition metal matrix composite material prepared in Example 1 reached adsorption equilibrium within 1 minute, with an adsorption capacity exceeding 1000 mg / g and a removal rate exceeding 99%, demonstrating performance far superior to the materials prepared in Comparative Examples 1, 2, and 3. This indicates that the magnetic transition metal matrix composite material prepared in Example 1 possesses highly efficient and excellent dye removal performance.
[0106] Figure 4 This is an adsorption curve of the magnetic transition metal matrix composite materials prepared in Examples 2, 4, and 5 of this invention. From... Figure 4 It can be seen that the materials prepared in Example 2, Comparative Example 4, and Comparative Example 5 all reached adsorption equilibrium at approximately 360 min. At 360 min, Example 2 exhibited the highest adsorption capacity for methylene blue, reaching approximately 1000 mg / g.
[0107] Figure 5 This is a graph showing the change in the removal rate of dyes of different concentrations by the magnetic transition metal matrix composite material prepared in Example 1 of this invention over time. Figure 5 It can be seen that the magnetic transition metal matrix composite material prepared in Example 1 has excellent adsorption performance for both low and high concentrations of methylene blue dye, which indicates that the magnetic transition metal matrix composite material prepared in Example 1 has broad practical application value in dye removal.
[0108] All aspects, embodiments, features, and examples of this invention are to be regarded as illustrative in all respects and are not intended to limit the invention, the scope of which is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0109] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.
[0110] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the described embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this invention is not intended to be limited to the specific embodiments disclosed for carrying out the invention, but rather is intended to encompass all embodiments falling within the scope of the appended claims.
Claims
1. A method for preparing a magnetic transition metal matrix composite material, characterized in that: A metal chelate is obtained by mixing and drying a metal salt solution with a ligand; the metal chelate is then calcined in a protective atmosphere to obtain a magnetic transition metal matrix composite material; wherein the metal salt in the metal salt solution includes at least one of nickel salt and iron salt.
2. The preparation method according to claim 1, characterized in that, include: Metal salts are mixed with water to form metal salt solutions; Preferably, the concentration of the metal salt solution is 0.1–3 mol / L.
3. The preparation method according to claim 1, characterized in that: The nickel salt includes at least one of nickel chloride, nickel sulfate, nickel nitrate, and nickel acetate; And / or, the iron salt includes at least one of ferric chloride, ferric sulfate, and ferric nitrate; And / or, the ligand comprises at least one of sodium citrate, sodium diethylenetriaminepentaacetate, disodium ethylenediaminetetraacetate, and sodium sulfosalicylate.
4. The preparation method according to claim 1, characterized in that, include: The complexing agent is mixed with water to obtain a complexing agent solution; Preferably, the concentration of the ligand solution is 0.1–3 mol / L; Preferably, the stirring is carried out at 50–100°C for 1–10 minutes.
5. The preparation method according to claim 4, characterized in that, include: The metal salt solution was mixed with the complexing agent solution to carry out a complexation reaction, and the metal chelate was obtained after drying. Preferably, the molar ratio of the metal salt to the ligand is 1:1 to 1:5; Preferably, the coordination reaction is carried out at a temperature of 50–100°C for a time of 2–6 hours. Preferably, the drying temperature is 50-100°C and the time is 8-24 hours.
6. The preparation method according to claim 5, characterized in that, Also includes: The metal chelate was calcined in a protective atmosphere, cooled, and then ground to obtain a magnetic transition metal matrix composite material. Preferably, the metal chelate is heated in a protective atmosphere at a rate of 2 to 10 °C / min; Preferably, the protective atmosphere includes nitrogen; Preferably, the calcination temperature is 700–850°C and the time is 60–180 min.
7. A magnetic transition metal matrix composite material prepared by any one of claims 1-6.
8. The application of the magnetic transition metal matrix composite material according to claim 7 in the field of dye wastewater treatment.
9. A method for treating dye wastewater, characterized in that, include: Provide the magnetic transition metal matrix composite material as described in claim 7; The magnetic transition metal matrix composite material is mixed with dye wastewater to carry out an adsorption reaction to adsorb the dye.
10. The method for treating dye wastewater according to claim 9, characterized in that: The dye includes methylene blue; And / or, the concentration of dye in the dye wastewater is 10–600 mg / L; And / or, the mass ratio of the magnetic transition metal matrix composite material to the dye is 1:1 to 1:3; And / or, the adsorption reaction is carried out at a temperature of 20–30°C for a time of 1–360 min; And / or, the method for treating dye wastewater achieves a dye removal rate of over 99%.